SYNTHESIS AND CHARACTERIZATION OF NEW AZO DYE (1-(4-SULFONYL PHENYL AZO)-2-(7-CHLORO-4-[{4-(DIETHYL AMINO)-1-METHYL BUTYL}AMINO]QUINDINE FROM CHLOROQUINE DIPHOSPHATE AND STUDY ANTIBACTERIAL ACTIVITY - Layla Addnan (Basrah Journal of Veterinary Research, 2016)
New azo dye was synthesized by reaction dizonium salt of sulfanilic acid with antimelaria drug (chloro quin diphosphate).This product was characterized by FTIR(Fourier Transform Infrared)andUV.Visible spectrophotometer .The antibacterial activities of the compound was studied and evaluated using gram positive and negative gram stain. The purity of the dye was checked by thin layer chromatography(TLC) using solvent system( sec.Butanol-water-acetic acid)(2:2:1).The melting point of the purified dye was measured in an open capillary tube. We have been concluded that the prepared azo dye showed antibacterial activity against this micro organism.